Lithuanian temporal adverbials: position in the system of temporal expressions and a review of semantic research - Makauskaitė, Indrė (Lietuvių kalba, 2016)
Expression of time is an important field in linguistic research. In Lithuanian linguistics, the study of time has focused first and foremost on tense and aspect systems. Therefore, Lithuanian language has developed a big diversity of means to encode time, e.g. noun cases (vasarą ‘in summer’) and noun phrases (liepos vakarą ‘in July evening’), prepositional phrases (po darbo ‘after work’), adverbs (netrukus ‘soon’), subordinate clauses (kai nustos lyti ‘when it stops raining’). All of them despite their different grammatical status are suggested to be called temporal adverbials. ‘Adverbial’ is a quite new notion in Lithuanian linguistics, it was first presented in the studies of stance adverbials but is also convenient in the field of linguistic expression of time. The purpose of the paper is to demonstrate the necessity of distinguishing a semantic-functional class of temporal adverbials in Lithuanian linguistics and to show their position in the system of means that encode time. The second part of the paper presents a few semantic models of the temporal adverbials made by foreign linguists and the semantic research of Lithuanian temporal means that should be regarded as temporal adverbials.